1958
DOI: 10.1038/hdy.1958.46
|View full text |Cite
|
Sign up to set email alerts
|

A new gene for deafness in the mouse

Abstract: Two years ago Deol (1956) reported the first case of inherited deafness in the mouse not associated with any of the usual concomitant locomotor disturbances. It was followed by a systematic search of the mouse colony of this laboratory, which resulted in the discovery of several other cases of the same kind. The mutant gene described here is one of them. The name deafness, symbol dn, is proposed for it. HEARING ABILITY AND BEHAVIOURHearing ability was tested by means of a click produced by striking a pair of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 1 publication
0
33
0
1
Order By: Relevance
“…In three families from Tamil Nadu in India showing recessive deafness, the defective gene was mapped to 9q13-q21, defining a new deafness locus (DFNB7/DFNB11) (Jain et al, 1995). The syntenic region in mouse also harbors a locus responsible for recessive deafness in the dn mouse (Deol and Kocher, 1958). showed in multiple families that the DFNB7/ DFNB11 gene, as well as those for the dominant human deafness DFNA36 and the dn mouse, encode a novel protein they called TMC1 (transmembrane cochlear-expressed gene 1, renamed transmembrane channel-like 1).…”
Section: Challenges For Molecular Identificationmentioning
confidence: 99%
“…In three families from Tamil Nadu in India showing recessive deafness, the defective gene was mapped to 9q13-q21, defining a new deafness locus (DFNB7/DFNB11) (Jain et al, 1995). The syntenic region in mouse also harbors a locus responsible for recessive deafness in the dn mouse (Deol and Kocher, 1958). showed in multiple families that the DFNB7/ DFNB11 gene, as well as those for the dominant human deafness DFNA36 and the dn mouse, encode a novel protein they called TMC1 (transmembrane cochlear-expressed gene 1, renamed transmembrane channel-like 1).…”
Section: Challenges For Molecular Identificationmentioning
confidence: 99%
“…To our knowledge, only two mouse mutations, deafness (dn) (Keats et al, 1995) and deaf (V df ) (Deol, 1956), have been reported that are not associated with balance or with other non-auditory defects. In contrast to the congenital, syndromic deafness caused by most mouse mutations, certain inbred strains of mice exhibit a progressive, non-syndromic hearing loss, with onset at more advanced ages.…”
Section: Introductionmentioning
confidence: 99%
“…They were provided by J, Goyens and E. Noirot, the latter having transferred the dn gene from litters of Deol's strain to a stock originating from the colony of outbrcd albino mice which she has described and has been maintaining since her first report (Noirot, 1964;Goyens & Noirot, 1974). Deol and Kocher (1958) have described the sequence of histopalhological changes in the ears of the homozygous (dnidn) animals. At birth, their inner ear structures appear normal.…”
Section: Methodsmentioning
confidence: 99%
“…Mutant mice earring the deafness (dn) gene described by Deol (1956) were used for this study. They were provided by J, Goyens and E. Noirot, the latter having transferred the dn gene from litters of Deol's strain to a stock originating from the colony of outbrcd albino mice which she has described and has been maintaining since her first report (Noirot, 1964;Goyens & Noirot, 1974).…”
Section: Methodsmentioning
confidence: 99%